Integrated genotype-phenotype analysis of familial adenomatous polyposis-associated hepatocellular adenomas - Tóth, Marcell; Kirchner, Martina; Longerich, Thomas; Stenzinger, Albrecht; Schirmacher, Peter (Virchows Archiv, 2023)
Familial adenomatous polyposis (FAP) is an autosomal dominant syndrome caused by a germline mutation in the adenomatous polyposis coli (APC) gene, characterized by numerous colorectal adenomas. In addition, FAP patients may develop extraintestinal manifestations. Several cases of hepatocellular adenomas (HCA) detected accidentally in FAP patients have raised the so-far unsolved question of whether they represent a specific manifestation of FAP or a mere coincidence. To investigate the incidence of liver tumors in FAP patients, we analyzed our diagnostic database from 1991 to 2021. Among the 58 hepatic mass lesions identified, five HCAs occurring in three patients with FAP were identified, and comprehensive morphological, immunohistological, and molecular analysis employing targeted next-generation sequencing was conducted for characterization. The HCAs in this study showed no cytological or histological atypia. They displayed a diffuse, strong positivity for glutamine synthetase but no nuclear beta-catenin immunostaining. In two patients, the adenomas showed moderate immunoreactivity against serum amyloid A. Consistent with the diagnosis of FAP, molecular profiling revealed a pathogenic germline mutation of the APC gene in all analyzed adenomas as well as deleterious somatic second hits. All somatic mutations were localized between codons 1345 and 1577. No mutations were found in the catenin beta 1 gene. HCA in FAP patients can be a specific, although rare, neoplastic manifestation of this inborn disease and represents a distinct subgroup of HCAs. These benign tumors represent an important differential diagnosis for hepatic metastases in FAP patients and require adequate clinical and molecular (diagnostic) assessments for optimal patient guidance.
Gesehen am 21.12.2023